2021
DOI: 10.3390/cells10040857
|View full text |Cite
|
Sign up to set email alerts
|

A Role for RAGE in DNA Double Strand Breaks (DSBs) Detected in Pathological Placentas and Trophoblast Cells

Abstract: Impaired DNA damage responses are associated with several diseases, including pregnancy complications. Recent research identified an ATM-kinase dependent function for the nuclear isoform of the receptor for advanced glycation end-products (RAGE) during double strand break (DSB)-repair. RAGE contributes to end-resectioning of broken DNA sites by binding with the MRE11-Rad50-Nbs1 (MRN) complex. Placental research is limited regarding the impact of genomic instability and the mechanism for potential repair. We te… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 34 publications
2
10
0
Order By: Relevance
“…As a result, it is difficult to know what specifically is driving the alterations in protein levels that we have seen with FAN1 in the IUGR placenta and how this also does not comport directly with the patterns we would typically expect to see in the regulation of gene expression by DNA methylation. Previous studies have shown increased placental DNA damage including increases in dsDNA damage in the PE placenta [ 41 , 42 ]. The fact that FAN1 expression is decreased suggests that perhaps this could be a factor involved in the increased placental DNA damage during this disease.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…As a result, it is difficult to know what specifically is driving the alterations in protein levels that we have seen with FAN1 in the IUGR placenta and how this also does not comport directly with the patterns we would typically expect to see in the regulation of gene expression by DNA methylation. Previous studies have shown increased placental DNA damage including increases in dsDNA damage in the PE placenta [ 41 , 42 ]. The fact that FAN1 expression is decreased suggests that perhaps this could be a factor involved in the increased placental DNA damage during this disease.…”
Section: Discussionmentioning
confidence: 99%
“…CRAB1 was a gene hypomethylated only in the IUGR placenta. As previously mentioned, this gene produces the cellular retinoic acid-binding protein that is responsible for the delivery of Retinoic Acid (RA) to its receptors [ 42 ]. In our studies, hypomethylation of this gene led to decreased expression of the CRAB1 protein.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This genotype is characterized by lower sRAGE levels and higher risk factors for CVD, which has implicated it in diabetes and autoimmune diseases, such as Kawasaki disease [ 25 ]. Thus, abnormal upregulation and sRAGE activation are indicative of disease development and inflammatory and immune responses in the body [ 28 , 103 , 152 , 153 ]. Generally, increased levels of membrane-bound RAGE are associated with disease pathogenesis/injury because the ligands bound to fl-RAGE are able to transduce that signal intracellularly and stimulate the nuclear translocation of NF-κB, thus producing inflammation.…”
Section: Rage As a Biomarker Or Putative Therapeutic Targetmentioning
confidence: 99%
“…Abnormal placentation characterized by morphological and histological alterations in the placenta could result in diverse pregnancy complications such as GDM, preeclampsia, miscarriage, intrauterine growth restriction, and stillbirth. Dysregulation of steroids hormones synthesis is one of the important signs of placental dysfunction in various pregnancy-associated complications [9, 12, 13]. In this regard, Shin et al [14, 15] reported the dysregulation of steroidogenesis-related enzymes as well as steroid production in different models of the preeclamptic placenta.…”
Section: Introductionmentioning
confidence: 99%